Construction of A Preliminary Three-Dimensional Structure Simian betaretrovirus Serotype-2 (SRV-2) Reverse Transcriptase Isolated from Indonesian Cynomolgus Monkey - Uus Saepuloh; Diah Iskandriati; Joko Pamungkas; Dedy Duryadi Solihin; Sela Septima Mariya; Dondin Sajuthi (Tropical Life Sciences Research, 2020)
Simian betaretrovirus serotype-2 (SRV-2) is an important pathogenic agent in Asian macaques. It is a potential confounding variable in biomedical research. SRV-2 also provides a valuable viral model compared to other retroviruses which can be used for understanding many aspects of retroviral-host interactions and immunosuppression, infection mechanism, retroviral structure, antiretroviral and vaccine development. In this study, we isolated the gene encoding reverse transcriptase enzyme (RT) of SRV-2 that infected Indonesian cynomolgus monkey (Mf ET1006) and predicted the three dimensional structure model using the iterative threading assembly refinement (I-TASSER) computational programme. This SRV-2 RT Mf ET1006 consisted of 547 amino acids at nucleotide position 3284–4925 of whole genome SRV-2. The polymerase active site located in the finger/palm subdomain characterised by three conserved catalytic aspartates (Asp90, Asp165, Asp166), and has a highly conserved YMDD motif as Tyr163, Met164, Asp165 and Asp166. We estimated that this SRV-2 RT Mf ET1006 structure has the accuracy of template modelling score (TM-score 0.90 ± 0.06) and root mean square deviation (RMSD) 4.7 ± 3.1Å, indicating that this model can be trusted and the accuracy can be seen from the appearance of protein folding in tertiary structure. The superpositionings between SRV-2 RT Mf ET1006 and Human Immunodeficiency Virus-1 (HIV-1) RT were performed to predict the structural in details and to optimise the best fits for illustrations. This SRV-2 RT Mf ET1006 structure model has the highest homology to HIV-1 RT (2B6A.pdb) with estimated accuracy at TM-score 0.911, RMSD 1.85 Å, and coverage of 0.953. This preliminary study of SRV-2 RT Mf ET1006 structure modelling is intriguing and provide some information to explore the molecular characteristic and biochemical mechanism of this enzyme.